ANALISIS PENGARUH PENILAIAN PRESTASI KERJA DAN KOMPETENSI KARYAWAN TERHADAP PROMOSI JABATAN PADA PT. XYZ - Nur Riani, Kisi; Rakhmat; Yesi, Reni (Mulia Pratama, 2024)
This research aims to determine the effect of partial work performance assessment on job promotion at PT. XYZ., to determine the partial influence of employee competency on job promotion at PT. XYZ, and to determine the effect of simultaneous assessment of work performance and employee competency on job promotion at PT. XYZ. The method used in this research is using probability techniques by random sampling from the population to be studied from employees at PT. XYZ. The data collection technique is carried out through primary data, namely by conducting a survey at PT. XYZ, and supported by related literature, journals and books as supporting data in conducting research. And the measurement tool used in data collection is the Likert scale. The results of analysis using multiple linear regression of the variables studied on the variable assessing employee work performance and competency regarding job promotion are Y=6.644 + 0.327 X1 + 0.471 X2. From this equation it can be seen that a: the constant number has a positive value, namely 6,644, this shows that if the job performance and competency assessment variables do not change or have a value of 0, then the value of job promotion is 6,644. b: The regression coefficient value of the work performance assessment variable is positive at 0.327, this shows that if the work performance assessment variable increases, then the position promotion variable will also increase by 0.327. c: The regression coefficient value for the employee competency variable is positive at 0.471, this shows that if the employee competency variable increases, then the position promotion variable will also increase by 0.471. Meanwhile, the coefficient of determination is 0.523, which means that the influence of the variable assessing work performance and employee competency simultaneously (together) has an influence of 52.3%, and the remainder is influenced by other variables or factors outside this research of 47.7%. . And the results of research testing also show that partial work performance assessment has an influence but is not significant on job promotion at PT. XYZ obtained from the t-test results with the t-static value on the work performance assessment variable is 0.932 with prob. of 0.356 (>0.05). Meanwhile, for the employee competency variable, there is a partial but not significant influence on job promotion at PT. XYZ obtained from the t-test results with the t-static value on the work performance assessment variable is 1.383 with prob. amounted to 0.174 (>0.05).